The physical literacy level of elementary school students was examined from the motivation and self-confidence domains - Irmansyah, Johan; Diningsih, Eka Safitri (Altius: Jurnal Ilmu Olahraga dan Kesehatan, 2024)
Physical education learning in elementary schools has a significant role in developing students’ physical literacy. However, physical literacy is not only related to physical abilities, but is also influenced by psychological factors, such as students’ motivation and self-confidence in the learning context. This study aims to analyze the domains of motivation and self-confidence using the Canadian Assessment of Physical Literacy (CAPL-2) Questionnaire in elementary school students. The design used in this research is a cross-sectional study design, which aims to collect data at one time (point time approach). The research results obtained that the percentage of motivation and self-confidence scores for elementary school students is as follows: beginning 0%; progressing 16.67%; achieving 33.33%; excelling 50%. The data shows that elementary school students have excellent levels of motivation and self-confidence (excelling category) and have exceeded the recommended physical literacy levels associated with substantial health benefits. In the context of physical education learning in primary schools, strengthening students’ motivation and building self-confidence will not only improve their physical skills, but will also help them develop positive attitudes towards physical activity and overall health.